Changes in micronutrient and inflammation serum biomarker concentrations after a norovirus human challenge. Issue 6 (30th August 2019) - Williams, Anne M; Ladva, Chandresh N; Leon, Juan S; Lopman, Ben A; Tangpricha, Vin; Whitehead, Ralph D; Armitage, Andrew E; Wray, Katherine; Morovat, Alireza; Pasricha, Sant-Rayn; Thurnham, David; Tanumihardjo, Sherry A; et al.
ABSTRACT: Background: To accurately assess micronutrient status, it is necessary to characterize the effects of inflammation and the acute-phase response on nutrient biomarkers. Objective: Within a norovirus human challenge study, we aimed to model the inflammatory response of C-reactive protein (CRP) and α-1-acid glycoprotein (AGP) by infection status, model kinetics of micronutrient biomarkers by inflammation status, and evaluate associations between inflammation and micronutrient biomarkers from 0 to 35 d post–norovirus exposure. Methods: Fifty-two healthy adults were enrolled into challenge studies in a hospital setting and followed longitudinally; all were exposed to norovirus, half were infected. Post hoc analysis of inflammatory and nutritional biomarkers was performed. Subjects were stratified by inflammation resulting from norovirus exposure. Smoothed regression models analyzed the kinetics of CRP and AGP by infection status, and nutritional biomarkers by inflammation. Linear mixed-effects models were used to analyze the independent relations between CRP, AGP, and biomarkers for iron, vitamin A, vitamin D, vitamin B-12, and folate from 0 to 35 d post–norovirus exposure. Results: Norovirus-infected subjects had median (IQR) peak concentrations for CRP [16.0 (7.9–29.5) mg/L] and AGP [0.9 (0.8–1.2) g/L] on day 3 and day 4 postexposure, respectively. Nutritional biomarkers that differed ( P  < 0.05) from baseline within the inflamed group were ferritin (elevated day 3), hepcidin (elevated days 2, 3), serum iron (depressed days 2–4), transferrin saturation (depressed days 2–4), and retinol (depressed days 3, 4, and 7). Nutritional biomarker concentrations did not differ over time within the uninflamed group. In mixed models, CRP was associated with ferritin (positive) and serum iron and retinol (negative, P  < 0.05). Conclusion: Using an experimental infectious challenge model in healthy adults, norovirus infection elicited a time-limited inflammatory response associated with altered serum concentrations of certain iron and vitamin A biomarkers, confirming the need to consider adjustments of these biomarkers to account for inflammation when assessing nutritional status. These trials were registered at clinicaltrials.gov as NCT00313404 and NCT00674336.